Crystallinity dependence for high-selectivity electrochemical oxygen reduction to hydrogen peroxide. Issue 39 (9th April 2020) - Liu, Meihuan; Zhang, Hui; Li, Yuanli; Su, Hui; Zhou, Wanlin; Zhao, Xu; Cheng, Weiren; Liu, Qinghua
Abstract : A modified-crystallinity structure of Ni3 (HITP)2 was designed to maximize the electrocatalytic selectivity toward H2 O2 production. Abstract : We report a semiconducting metal–organic graphene analog, Ni3 (HITP)2, with an adjustable crystalline structure for mediating efficient selectivity toward hydrogen peroxide. The as-prepared 5-Ni3 (HITP)2 catalyst with low crystallinity can electrocatalyze O2 to H2 O2 with a high selectivity of 80% over a wide potential range of 0.2–0.6 V vs. RHE and with a large mass activity of 292 A gNi −1 at 0.25 V in 0.1 M KOH.